PENGETAHUAN, SIKAP DAN PERILAKU PENGGUNAAN KONDOM PADA GAY ODHA DI RSUD KABUPATEN TANGERANG - Nurrohmah, Mey; Waluyo, Agung; Jumaiyah, Wati; Azzam, Rohman (Journal of Islamic Nursing, 2020)
Homosexuals are the group with the highest percentage who have sex with multiple partners and are at risk of contracting HIV-AIDS, therefore Homosexual (gay) is the orientation of individuals with others of the same sex either consciously or unconsciously. The purpose of this study was to determine the relationship of knowledge and attitudes with the behavior of condom use in homosexual PLHAs. This research is a descriptive correlation study with a cross-sectional approach (cross sectional), namely the measurement of the independent variable and the dependent variable carried out simultaneously with a sample of 64 out of 179 homosexuals. Measurement of variables is done by direct interview using a questionnaire. Data analysis uses the chi-square statistical test . The results of the study based on the age of the most aged <30 years as many as 39 people (60.9%), based on the education of the majority of respondents, namely high school as many as 51 people (79.7%). from the results of the bivariate analysis that there was no significant relationship between education and the attitude of the use of condoms to the compliance of condom use in homosexual PLHAs (p = 0.638) . Can be used as a reference in preventing the increase in HIV / AIDS among the community through various kinds of training for people who will be involved in conducting counseling and direct guidance to the community about HIV/AIDS and can provide information about HIV/AIDS to the community and provide motivation for sufferers to continue to live. Keywords: condom use behavior , HIV / AIDS, homosexuality (gay)